IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE USE OF PEN TABLET WITH ZOOM APPLICATION - Imroatus Sholekhah (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
This Best Practice writing aims to describe the improvement of mathematics learning outcomes through the use of a Pen Tablet with the Zoom application. The subjects of this best practice writing are students of class XII MIPA-3 SMAN 2 Tanggul in the odd semester 2021/2022 academic year, totaling 34 students on the Derivatives of Trigonometric Functions. Quantitative data were obtained from quiz scores and daily tests using multiple choice written test techniques using Google Form. From the implementation of mathematics learning using a pen tablet and the Zoom application, an increase in student learning outcomes was obtained, seen from the average value and classical student learning completeness. The average score for quiz 1 is 64.12 and quiz 2 is 79.12. This means that from quiz 1 to quiz 2 there is an increase of 15% From quiz 2 with an average of 79.12 to daily tests to 86, 76 increased by 7.64% . Judging from the mastery of learning also increased. Quiz 1 learning completeness classically is 32.35%, quiz 2 is 70.59%, and daily test is 85.29%. This means that there is an increase from quiz 1 to quiz 2 by 38.24% while from quiz 2 to daily tests it increases by 14.7%. This best practice shows an increase in mathematics learning outcomes through the use of a Pen Tablet with the Zoom application, especially for class XII MIPA-3 students of SMAN 2 Tanggul in the odd semester of the 2021/2022 academic year.